GE_GERICHTE P/15141/2023 vom 7. Mai 2025 - GE Cour de justice (2025)
MANIFESTATION;CONTRAVENTION;ORDONNANCE PÉNALE;SIGNATURE;DÉCISION DE RENVOI | LMDPu.10; CPP.398.al4; CPP.353.al1.letK; CPP.357.al1; CPP.357.al2; CPP.356.al2; CPP.356.al5